Effectiveness of a live-chat social media and leaflets for people living with HIV/AIDS (PLWHA) under antiretroviral therapy (ARVs) - Tri Okta Ratnaningtyas; Fenita Purnama Sari Indah; Ayatun Fil Ilmi (Malahayati International Journal of Nursing and Health Science, 2022)
Background: Adherence to taking ARV (antiretroviral) is a term used to describe the patient's behavior in taking medication correctly regarding dose, frequency, and time. To get a response to suppress the number of viruses up to 85%, 95% compliance is required in the use of drugs. Failure to achieve adherence rates of less than 95% will reduce the suppression of HIV replication. In general, non-compliance is explained.Purpose: To analyze the effectiveness of live-chat social media and leaflets for people living with HIV/AIDS (PLWHA) under antiretroviral therapy (ARVs)Method: This study uses a quantitative approach. This research is pre-experimental research with one group pretest and posttest design. In this study, respondents were given treatment using live-chat social media and leaflets within 4 (four) weeks. Every week respondents are given 2x a live-chat social media and leaflets. Posttest 1 for knowledge, attitudes, and practice of adherence to antiretroviral therapy was conducted after 2 weeks of intervention, while posttest 2 was conducted after 4 weeks of intervention. The sample in this study were all PLWHA (People With HIV/AIDS) in PSG (Peer Support Groups) who were willing to become research respondents, as evidenced by filling out the informed consent given by 30 PLWHA.Results: There is a difference in knowledge, attitude, and adherence to ARV between pre-test and post-test 1 by live-chat social media and leaflets with a p-value < 0.05. Likewise, with the results between post-test 1 and post-test 2, there are differences in knowledge, attitudes, and adherence to taking ARV between post-test 1 and post-test 2 by live-chat social media and leaflets.Conclusion: The intervention of live-chat social media and leaflets is effective in increasing knowledge, attitude, and adherence to taking ARV in PLWHA (People Living with HIV/AIDS).